A social work study on family patterns and street children - Mohammad Reza Iravani; Samaneh Salimi; Seyed Mohsen Khalifeh Soltani; Shahram Basity (Management Science Letters)
This paper presents a social work study on relationship between various family characteristics and street children in rural area as well as city of Esfahan, Iran. The proposed study selects a sample of 150 street children, 75 from city and 75 from rural area, and using some statistical tests verifies the effects of three factors including family income, place of residency and family size on street children. The results indicate that the city residence had more street children than rural residence did. In addition, there was a meaningful difference between the number of street children in low-income families and high-income families. Finally, the survey results indicate that big size families more likely suffered from street children than low size families did.